Effect Combination of HIIT with Recovery Model on VO2max Quality and Monitoring of Heart-Rate Recovery - Kurniawan, Candra; Priyono, Dwi; Firmansyah, Guntur (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
This study aims to analyze the effect of differences resulting from the combination of HIIT with recovery models in active and passive forms on the quality of VO2max and monitoring of heart-rate recovery. This study was designed using a quasi-experimental design, and 30 participants participated voluntarily in the study which was further divided into three groups: HIIT-PP experiment (n:10; Age: 21.0±0.82; Weight: 67.2±13.6; Height: 1.68±0.07), HIIT-PP experiment (n=10; Age: 21.1±1.20; Weight: 64.9±6.07; Height: 1.68±0.04), and control group (n=10; Age: 21.09±1.29; Weight: 69.3±5.46; Height 1.69±0.05). This research instrument uses Multistage Fitness Test (MFT) and Heart-Rate Monitoring. The procedure for analyzing the statistical research data used the Analysis of Variance (ANOVA) test with a p-value <0.05. The results showed that the parameter differences between the experimental and control groups significantly improved the quality of VO2max and monitoring of heart-rate recovery (HRM, and HRR 2min, 5min, 10min). This study can conclude that using HIIT with recovery models in passive forms for eight weeks resulted in a change in the quality of VO2max and monitoring of heart rate recovery.